Ant type specimens (Hymenoptera, Formicidae) in the collection of Volodymyr Opanasovych Karawajew. Communication 4 (concluding). Myrmicinae - Radchenko, Alexander G.; Fisher, Brian L.; Esteves, Flavia A.; Martynova, Ekateryna V.; Bazhenova, Tatyana N.; Lasarenko, Svetlana N. (Zootaxa, 2026)
The article is the fourth (and final) in a series of catalogues of ant type specimens from the collection of V. O. Karawajew (1864–1939), stored at the I.I. Schmalhausen Institute of Zoology of the National Academy of Sciences of Ukraine (SIZK, Kiev). This work includes data on 1530 type specimens (17 holotypes, one lecotype, 191 paralectotypes, one neotype and 1320 syntypes) from 220 taxa of the subfamily Myrmicinae, collected from around the world and described by Karawajew and other myrmecologists, which are currently assigned to 31 genera (Acromyrmex, Aphaenogaster, Apterostigma, Bondroitia, Cardiocondyla, Carebara, Cephalotes, Chelaner, Crematogaster, Goniomma, Lophomyrmex, Meranoplus, Messor, Monomorium, Mycocepurus, Myrmecina, Myrmica, Myrmicaria, Ocymyrmex, Oxyopomyrmex, Pogonomyrmex, Pheidole, Podomyrma, Pristomyrmex, Solenopsis, Stenamma, Strongylognathus, Strumigenys, Temnothorax, Tetramorium and Trichomyrmex).